2013
DOI: 10.1109/tie.2011.2171176
|View full text |Cite
|
Sign up to set email alerts
|

General Analysis on the Use of Tesla's Resonators in Domino Forms for Wireless Power Transfer

Abstract: In this paper, we present a brief overview of historical developments of wireless power and an analysis on the use of Tesla's resonators in domino forms for wireless power transfer. Relay resonators are spaced between the transmitter and receiver coils with the objectives of maximizing energy efficiency and increasing the overall transmission distance between the power source and the load. Analytical expressions for the optimal load and maximum efficiency at resonance frequency are derived. These equations are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
158
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 313 publications
(166 citation statements)
references
References 27 publications
1
158
0
Order By: Relevance
“…8. It is found that the transmission distance has a great effect on the transmission efficiency of the domino MCR-WPT system [15], but, the transmission distance of the DS MCR-WPT has no effect on the transmission efficiency. The DS MCR-WPT system is a better solution to the problem which the CC between non-adjacent coils caused by frequency drift, efficiency the system.…”
Section: Parametric Analysis Of Traditional Domino Wpt Systemmentioning
confidence: 93%
See 3 more Smart Citations
“…8. It is found that the transmission distance has a great effect on the transmission efficiency of the domino MCR-WPT system [15], but, the transmission distance of the DS MCR-WPT has no effect on the transmission efficiency. The DS MCR-WPT system is a better solution to the problem which the CC between non-adjacent coils caused by frequency drift, efficiency the system.…”
Section: Parametric Analysis Of Traditional Domino Wpt Systemmentioning
confidence: 93%
“…9(a). The output and input voltage values are measured using an oscilloscope, and the output and input power values can be obtained, so the system transmission efficiency can be obtained [15]. The measured value load voltage V L and the system transmission efficiency along the frequency curve was determined per the oscilloscope range from 82.0 kHz and 90.0 kHz and compared to the calculated values, as shown in Fig.…”
Section: Experimental Validation Of Ds Mcr-wpt Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Kim et al [9] pointed out that either a coaxially arranged relay coil or a perpendicularly arranged relay coil can considerably improve the system power transfer efficiency. Zhong et al [10] also analyzed the power transfer characteristics of multi-relay coils system using the Recently, wireless power transfer is also being used at subgigahertz (GHz) frequency to capsule endoscope where compact self-resonant antennas are designed to realize the transcutaneous power transfer [11]. It is commonly believed that efficient WPT to implantable devices require RF transmission frequency in the low MHz range to avoid excess losses in tissues.…”
Section: Introductionmentioning
confidence: 99%